Attachment of Vibrio cholerae serogroup O1 to zooplankton and phytoplankton of Bangladesh waters. - Tamplin, M L (1990)
Vibrio cholerae serogroup O1, the causative agent of cholera, is capable of surviving in aquatic environments for extended periods and is considered an autochthonous species in estuarine and brackish waters. These environments contain numerous elements that may affect its ecology. The studies reported here examined physical interactions between V. cholerae O1 and natural plankton populations of a geographical region in Bangladesh where cholera is an endemic disease. Results showed that four of five clinical V. cholerae O1 strains and endogenous bacterial flora were attached preferentially to zooplankton molts (exuviae) rather than to whole specimens. One strain attached in approximately equal numbers to both exuviae and whole specimens. V. cholerae O1 also attached to several phytoplankton species. The results show that V. cholerae O1 can bind to diverse plankton species collected from an area where cholera is an endemic disease, with potentially significant effects on its ecology.